(untitled) (Proceeding of SINERGY, 2026)
This research investigates how the work environment, organizational commitment, work motivation, and organizational culture affect the level of employee work spirit at PT. Slamet Langgeng Purbalingga. The total workforce numbered 168 individuals, and 123 of them were chosen as research participants through a proportionate stratified random sampling technique. The collected data were processed using multiple linear regression supported by SPSS. The statistical calculation produced the equation: Y = −2.513 + 0.145X₁ + 0.137X₂ + 0.202X₃ + 0.320X₄ + e. The coefficient of determination (R²) reached 0.612, which means that 61.2% of the fluctuations in employee work spirit can be accounted for by the four independent variables, while the remaining 38.8% is attributed to other unexamined influences. The simultaneous test demonstrates that the regression model is significant, as indicated by F = 46.492 exceeding the F-table value of 2.4485. Partial testing further reveals that each independent variable contributes positively and significantly to employee work spirit, with organizational culture emerging as the most dominant contributor. These outcomes imply that company management should focus on cultivating a strong organizational culture, boosting employee motivation and commitment, and creating a conducive workplace atmosphere to elevate both employee enthusiasm and overall organizational performance. It is also suggested that subsequent research expand the scope by including additional determinants such as leadership style, compensation systems, and job satisfaction to achieve a broader understanding of factors shaping employee work spirit.